What can we do to support reading for young adolescent students?. Issue 2 (4th March 2017) - Fletcher, Jo
Abstract : Young adolescents are at a critical stage in their schooling. They are consolidating and improving their reading skills. By exploring what supports these 11- to 13-year-old students in reading from a wider systemic perspective, educators and policy-makers can better understand the complex factors which support reading development. This article presents a conceptual framework model to illustrate how teachers, principals and wider support agencies can effectively interact with the students and their parents. The framework highlights the impacting roles of ministries of education, governmental policies, and how study at postgraduate level can support reading development for these young adolescents.